Pengembangan komponen kompetensi kewargaan dalam buku teks Pendidikan Kewarganegaraan SMP/MTs - Arif, Dikdik Baehaqi (Jurnal Civics: Media Kajian Kewarganegaraan, 2016)
This essay was aimed at describing the development of civic knowledge, civic skill and civic disposition on textbooks for junior high school namely "Belajar Memahami Kewarganegaraan 1, 2 and 3". Based on content analysis, it can be conducted that civic education element was developed through teaching material presented accompanied by features, such as additional boxes, every chapter including pictures, law corner, info, public figures, and citizenship dictionary. In addition to presentation of civic skill related teaching material, box of "uji kompetensi" was utilize to enhance civic skill competences. Civic disposition was enhanced by inserting national values as well as up-held-values but conceptually.